Stressful Life Events and Obesity in the United States: The Role of Nativity and Length of Residence. Issue 1 (January 2022) - Cuevas, Adolfo G.; Stanton, Michael V.; Carvalho, Keri; Eckert, Natalie; Ortiz, Kasim; Assari, Shervin; Ransome, Yusuf
Purpose: Obesity is a public health issue in the United States (US), that disproportionately affects marginalized group members. Stressful life events (SLE) have been implicated as an obesogenic risk factor. However, there is scant research examining of the role of nativity status and length of residence in the relationship between SLE and obesity. Design: Cross-sectional survey. Setting: Wave 2 of the National Epidemiologic Survey on Alcohol and Related Conditions. Sample: A total of 34, 653 participants were included in these analyses, of whom 10, 169 (29.39%) had obesity. Measures: Obesity (measured using body mass index), stressful life events, race/ethnicity, gender, educational attainment, family income, marital status, current smoking status, and alcohol abuse. Analysis: Weighted logistic regression analysis. Results: A total of 10, 169 (29.39%) had obesity. There was a significant interaction between SLE and nativity status/length of residence [F (3, 34, 642) = 60.50, p < 0.01]. Based on stratified analyses, SLE were associated with greater odds of obesity for US-born individuals (OR = 1.07; 95% CI [1.05, 1.08]) and foreign-born individuals living in the US for ≥ 20 years (OR = 1.17; 95% CI [1.10, 1.25]). There was no evidence that SLE were associated with greater odds of obesity for foreign-born individuals living in the US <10 years (OR = 1.06; 95% CI [0.94, 1.21]) and 11-19 years (OR = 1.00; 95% CI [0.91, 1.09]). Conclusions: Number of SLE may be a risk factor for obesity, particularly for US-born adults and foreign-born adults living the US >20 years. Further research is needed to understand the pathways that may link SLE to obesity among these groups.